GAMBARAN SANITASI DASAR MASYARAKAT WILAYAH PESISIR - Siti " Rohmi; Febriana " Sabrian; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractBasic sanitation is the minimum health requirements the family must have to meet their daily needs, that conducted by the communities as a step of preventing disease. Basic sanitation includes clean water supply, disposal of human waste, waste management and wastewater disposal. This research aims identify at the knowledge, attitudes and communities’ practice about basic sanitation in Meranti Pandak, Rumbai Pesisir. This research involves 265 samples that were taken by probability sampling techniques. The analysis used is univariate analysis. The results show that the majority of respondents are 18-35 years old (66.8%), the gender are women (78.9%), the majority of respondents are housewives (70.6%), the background of education is senior high school (39.6%). About 39.6% of the respondents have a good knowledge about basic sanitation, 50.9% of the respondents have positive attitudes towards basic sanitation and 59.6% of the respondents have good practice of basic sanitation. An aspect that need to be improved related to the knowledge about basic sanitation is the aspect of wastewater disposal. With regardes to the attitudes, the aspect of waste managements needs improvement. Based on the results of research, it is expected that public health centers and related health institutions continue to provide education and increase motivation of communities in order to improve the quality of basic sanitation practice. Keywords              : Attitude, basic sanitation, knowledge, practice.